2020
DOI: 10.1016/j.eats.2019.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Two-Stage Anterior Cruciate Ligament Reconstruction Revision Surgery for Severe Bone Defects With Anterolateral Ligament Reconstruction Technique

Abstract: Anterior cruciate ligament revision surgery poses a number of specific difficulties. These include the lack of bone mass to enable effective fixation of the reconstruction, morbidity of the donor area when bone autograft is used to fill the tunnels, and absence of the semitendinosus and gracilis homolateral tendons in cases in which they have already been used in the primary surgical procedure. To address all these problems, we describe a 2-stage revision technique that uses bone allograft for tunnel filling a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Fernandez et al. [ 24 ] described a long Achilles tendon technique for revision ACL reconstruction and ALL reconstruction, but the authors performed the procedure in two stages and with the medial tibial tunnel, precisely to fill the bone defects initially, different from our proposal for single-stage reconstruction with an anterolateral tibial tunnel. Slope correction osteotomies also can be indicated in a re-revision ACL reconstruction, but this procedure is normally indicated in patients with at least 13° of tibial slope.…”
Section: Discussionmentioning
confidence: 94%
“…Fernandez et al. [ 24 ] described a long Achilles tendon technique for revision ACL reconstruction and ALL reconstruction, but the authors performed the procedure in two stages and with the medial tibial tunnel, precisely to fill the bone defects initially, different from our proposal for single-stage reconstruction with an anterolateral tibial tunnel. Slope correction osteotomies also can be indicated in a re-revision ACL reconstruction, but this procedure is normally indicated in patients with at least 13° of tibial slope.…”
Section: Discussionmentioning
confidence: 94%
“…Additionally, this technique has the advantage of being easy to apply in cases of revisional reconstructions, where the use of autografts is difficult. Finally, although some studies reported ALL reconstruction techniques using a single bundle graft [ 20 , 21 ], the ALL is reconstructed using two tibial bony sockets with two graft bundles in this technique [ 22 , 23 , 24 ]. The two tibial sockets in this novel technique may have the advantage of restoring the broad base of the anatomic ALL tibial footprint.…”
Section: Discussionmentioning
confidence: 99%
“… 18 , 19 , 20 , 21 The critical problems during the preparation relate to mismatched dimensions; incorrect thawed, prophylaxis; bone marks and cuts; excessive bone removal; fracture of the bone block by dilation; or allograft contamination. However, support for the important use advantages of the Achilles allograft is given in Table 2 , advantages that include a standardized preparation ( Table 1 ) that helps provide adequate dimension of the allograft, 4 easy manipulation in the operative room, fast procedure, nonmorbidity by the donor site, high strength, healing advantages, multiple-ligament reconstruction capacity, potential to fill bone defects, 14 a high rate of a successful return to sports, 3 and diminished chance of graft tunnel mismatch.…”
Section: Discussionmentioning
confidence: 99%
“…28 No donor site morbidity 28 Graft length allows direct traction over the tendon during the insertion of the tibial implant Fixation without needing sutures or traction. Anatomical fixation by bone-to-bone at the femoral insertion (healing advantages) Multiple-ligament reconstruction 14 The bone block allows filling bone defects (mainly revision cases) 14 Avoid a two-stage ACL revision Allows free tendon fixation in case of bone block loss No lower clinical differences in ACL reconstructions compared with other allografts 29,30 High rate of successful sport returns up to 81% of athletes at 6 years mean follow-up 3 Allows primary and revision surgery High tensile resistance of the allograft 19 Limitations Disease transmission, i.e., the immunodeficiency virus reported 1 case of 1.6 million cases (a small risk) 23 Slower time for graft integration like any bone-to-bone healing 24 In some centers, it could be an expensive procedure Fracture of the bone block by dilation ACL, anterior cruciate ligament.…”
Section: Discussionmentioning
confidence: 99%